Popliteal artery injury following traumatic knee joint dislocation in a 14-year-old boy: A case report and rewiev of the literature - Cvetković, Slobodan; Jakoviljević, Nenad; Simić, Dušica; Sladojević, Miloš; Djurašić, Ljubomir; Davidović, Lazar (Vojnosanitetski pregled, 2013)
Introduction. Posterior knee joint dislocation associated with injury of the popliteal artery in children is an extremely rare condition. Rapid diagnosis and treatment are essential for limb salvage and function. Case report. We reported a 14-year-old boy who suffered traumatic displacement of the right knee and contusion of the popliteal artery during motorcycle accident. The diagnosis was confirmed using Doppler and duplex ultrasonography and digital substraction transfemoral arteriography. The urgent surgical procedure was performed using posterior approach to the popliteal artery. During the surgical exploration, rupture of the posterior cruciate ligament associated with thrombosed popliteal artery have been found. The damaged popliteal artery was resected and replaced with autologous saphenous vein graft. The last stage of the procedure was a transosseous femoral fixation of posterior circuate ligament. A 3-year-follow-up after the surgery demonstrated intact arterial perfusion and very good function of the knee with a minimal difference as compared with the contralateral knee. Conclusion. Combined orthopedic and vascular injuries are very rare in children. They require combined treatment.